A construção da autonomia e do reconhecimento na transição agroecológica - Sena, Maurício Machado (2018)
The present work investigates the construction of autonomy and recognition among four agricultural families in Agroecological transition. Revealing the importance of farmers' experiences and their relationship with agroecosystems, in the construction of knowledge, exchange of wisdom and in teaching/learning relationships. From this perspective we approach Sustainability from the Ethics dimension, communication based on Dialogue and Communicative Action and Agroecology as a field of knowledge. The research uses documents, interviews, photographs and audiovisual material collected between August 2017 and January 2018. They are part of this experience farming families who participated in the NEA-UFSM shares in the period and share some similarities. We think of Participatory Methodologies as a possibility of investigation and the audiovisual as a potentiator of the experience of encounter the need for social transformation. Thus, we first investigate the motivations and expectations of farmers, revealing the role of Agroecology and Communicative Action in family relationships. We question the social relations established in the agroecosystems from the generative themes, stressing questions about the agroecological practices as foment to a "good life". We also investigate the ethical dimension, interpersonal relations and the search for autonomy and recognition relating them to the quality of life. And we developed the idea of audiovisual as an element of knowledge construction and return to farmers. As final considerations we revealed the need to construct the pertinent questions to Agroecology from the farmers world view and we witnessed, in the communication, an adequate path for this attempt, identifying it as a fundamental element in this process. We also point out the need to construct a new rationality based on Participatory Methodologies. Through the Generating Themes we perceive affectivity and personal relationships as guiding elements of farmers' actions. From the communication these themes, inherent to the World of Life, can be constructed and re-signified aiming at the colonization of the System World. Thus, we point out that Audiovisual is an important contribution in the exercise of revealing these experiences, being used as a participatory tool and instrument of return and recognition for these families. This movement of participatory research and feedback has revealed that communication contributes to the construction of autonomy and recognition of these farmers, providing means for social transformation.